2011
DOI: 10.1158/0008-5472.can-10-1088
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-PET Imaging Is a Noninvasive Biomarker Showing Differential Changes in the Tumor during Sunitinib Treatment

Abstract: Non-invasive imaging of angiogenesis could ease the optimization of antiangiogenesis treatments for cancer. In this study, we evaluated the role of VEGF-PET as a biomarker of dynamic angiogenic changes in tumors following treatment with the kinase inhibitor sunitinib. The effects of sunitinib treatment and withdrawal on the tumor was investigated using the new VEGF-PET tracer 89

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 35 publications
2
67
0
Order By: Relevance
“…Tumor 89 Zr-bevacizumab uptake decreased during treatment in lung and brain metastases but increased in normal liver and bone metastases, with reverse pattern after 2 drug-free weeks. The small decrease that we observed in mean tumor 89 Zrbevacizumab uptake after 2 wk of sunitinib and the rebound exceeding baseline after 2 wk off treatment correspond with our preclinical findings (27). Preclinical studies showed increased invasiveness and metastasis after a short sunitinib course (4,5).…”
Section: Discussionsupporting
confidence: 86%
“…Tumor 89 Zr-bevacizumab uptake decreased during treatment in lung and brain metastases but increased in normal liver and bone metastases, with reverse pattern after 2 drug-free weeks. The small decrease that we observed in mean tumor 89 Zrbevacizumab uptake after 2 wk of sunitinib and the rebound exceeding baseline after 2 wk off treatment correspond with our preclinical findings (27). Preclinical studies showed increased invasiveness and metastasis after a short sunitinib course (4,5).…”
Section: Discussionsupporting
confidence: 86%
“…Although several of these tracers have been tested in a preclinical and clinical setting in which they successfully visualized several types of tumors and their metastases (15,16), none of these are routinely used in the clinic and few have been used to detect antiangiogenic therapy response. In 2 studies, response to antiangiogenic therapy was successfully detected using 99m Tc-hydrazinonicotinamide-VEGF and 89 Zr-ranibizumab (17,18). However, because of the long biologic half-life of VEGF, labeling of VEGF or VEGF-targeting molecules with long-lived iso- topes such as 89 Zr or 111 In is needed (18,19), resulting in high radiation exposures.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 studies, response to antiangiogenic therapy was successfully detected using 99m Tc-hydrazinonicotinamide-VEGF and 89 Zr-ranibizumab (17,18). However, because of the long biologic half-life of VEGF, labeling of VEGF or VEGF-targeting molecules with long-lived iso- topes such as 89 Zr or 111 In is needed (18,19), resulting in high radiation exposures. Using RGD (asparagine-glycineaspartic acid) peptide-based tracers, several studies also successfully evaluated treatment response to antiangiogenic therapy (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…It is already proven with numerous antibodies (39,(70)(71)(72)(73)(74) and other proteins (75,76) through the efforts of groups in The Netherlands where it has been developed in both preclinical and, with good manufacturing practices (GMP) production for tracer production and validation, in clinical settings. Although Zr-89 does have an extraneous high-energy gamma ray (909 keV), the image quality is good and the overall radiation burden is well tolerated (77).…”
Section: The Advent Of Zirconium-89mentioning
confidence: 99%